PENINGKATAN LITERASI KEUANGAN DAN INKLUSI KEUANGAN BAGI MASYARAKAT DESA BENOA KECAMATAN KUTA SELATAN - I Made Wisnu Wardana; Ni Luh Wulani Parwati; Fahmi Tanjung; I Made Sujana (Nusantara Hasana Journal, 2022)
This Community Service program aims to improve financial literacy and financial inclusion among the people of Benoa Village, South Kuta District, Badung Regency. The community's lack of understanding of financial management, the use of banking products, and digital financial services is one of the obstacles to improving the community's economic well-being. Good financial literacy can help the community understand the risks and benefits of various financial products, enabling them to make wise economic decisions. The community service program is carried out through outreach, training, mentoring, and interactive discussions on household financial management, savings, investments, and the use of digital financial services. The results of the activity indicate an increase in participants' understanding of financial management and access to formal financial institutions, which is expected to encourage improved welfare for the Benoa Village community.